OPTIMIZING DATA TRANSFER COSTS: A TECHNICAL GUIDE - Srianusha Kuchipudi, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
The rapid evolution of cloud computing has made data transfer costs a critical concern for organizations worldwide. This comprehensive article explores cloud data transfer operation's fundamental cost drivers, challenges, and optimization strategies. The article examines bandwidth consumption patterns, data volume management, transfer frequency optimization, and geographic considerations that impact transfer costs. It presents technical strategies for cost reduction, including delta and incremental transfers, cloud architecture optimization, direct transfer paths, and centralized collaboration solutions. The article also delves into implementation considerations, covering baseline metrics, monitoring systems, automation strategies, and success metrics. Through analysis of industry research and case studies, this article demonstrates how organizations can significantly reduce their data transfer costs while maintaining operational efficiency by strategically implementing optimization techniques.